Radiofrequency ablation versus traditional liver resection and chemotherapy for liver metastases from gastric cancer. Issue 7 (July 2020) - Tang, Kezhong; Zhang, Bo; Dong, Linping; Wang, Lantian; Tang, Zhe
Objective: To compare the short- and long-term outcomes of radiofrequency ablation (RFA) versus liver resection and chemotherapy for liver metastases from gastric cancer. Methods: We retrospectively evaluated 50 patients who underwent curative gastrectomy and local treatments for liver metastases (RFA, n = 20; liver resection, n = 20; and chemotherapy, n = 10) from 2008 to 2018. Results: The short- and long-term outcomes of each local treatment were evaluated. The median overall survival (OS) after RFA was similar to that after liver resection (20 vs. 20 months, respectively) and longer than that after chemotherapy (20 vs. 10 months, respectively). The 3-year OS and progression-free survival (PFS) rates after RFA were 20% and 10%, respectively, while those in the liver resection group were 23.5% and 23.5%, respectively. The 3-year OS rate after chemotherapy was 10%. The size and number of metastases were prognostic factors for patients with gastric cancer with liver metastasis without statistical significance. Conclusions: Among patients with liver metastasis from gastric cancer, OS and PFS were satisfactory and comparable between RFA and liver resection but better than those of chemotherapy. RFA is an appropriate option for patients with gastric cancer who have a solitary liver metastasis measuring ≤3.0 cm.